MODEL PENGEMBANGAN KAPASITAS PENDAMPING DI RUMAH CINTA DISABILITAS INTELEKTUAL (RCDI) KECAMATAN LEMBANG KABUPATEN BANDUNG BARAT - Triastuti Anggra Dewi; Aep Rusmana; Pribowo Pribowo (Politeknik Kesejahteraan Sosial Bandung, 2022)
Capacity building for mentors is an effort made to strengthen and increase the potential of mentors in providing social rehabilitation services at RCDI (House of Love for Intellectual Disabilities) Lembang Sub District, West Bandung District. The purpose of this study was to examine: the description of the research subject, the initial model before carrying out the capacity development, the planning model for the capacity development, the implementation model for the capacity development, and the final model for developing the capacity. The research method used is Participatory Action Research (PAR). Data collection techniques used in-depth interviews, participatory observation, documentation studies and Focus Group Discussions. The results of the study provide an overview: (1). RCDI assistants are disability assistance workers appointed by the West Bandung District Social Office (2). The initial model of capacity building was based on the duties and responsibilities of the assistants which consisted of: data verification, assistance, guidance (physical, mental, social and skills), education and motivation for intellectual disability families, home visits, and implementation reporting. activity. (3). The planning model is described in input, process, output and outcome. (4). The implementation model consists of improving: assessment, service planning, vocational skills and evaluation. (5). The final model is the result of refinement of the initial model and implementation model.